Climate Change-Based Report Texts For Senior High School : a Mix Method Study - Tenridinanti, Tamara Becce; Inderawati, Rita Becce; Mirizon, Soni (FKIP Universitas Lampung, 2021)
Climate Change-Based Report Texts For Senior High School : a Mix Method Study. Objectives: This research aimed to uncover the needs of high school students to develop English reading material based on climate change and examined by perspectives of students, English teacher, and stakeholders. Methods: This study used mix method. Participant of this study was the eleventh-grade students, English teachers, and other school stakeholders. Data were obtained using a questionnaire and semi-structured interviews. Findings: Result of needs analysis showed that: 1) students still had difficulty understanding the text. 2) type of text needed was report text, 3) students did not still know about climate change, 4) main reason for including climate change in reading was to encourage motivation English. Conclusion: Due to the need, it was necessary to develop supplementary report text reading materials incorporating climate change to suit the students’ English proficiency.Keywords: English reading materials, Senior High School, climate change, need analysis.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202112